Clinico-Immunobiochemical Markers of Destructive Cholecystitis: Penanda Klinis-Imunobiokimia pada Kolesistitis Destruktif - Abdullokulov Umid Maxmudjonovich; Fayzullaeva Nigora Yakhyayevna; Abdumajidov Abdugafur Shukurovich; Zuparov Kamoliddin Farkhadovich (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Gallstone disease and its inflammatory complications remain a major concern in hepatobiliary surgery, with destructive cholecystitis frequently associated with severe postoperative morbidity. Specific Background: Progression from chronic calculous cholecystitis to acute purulent-destructive forms involves systemic inflammatory activation, metabolic disturbances, and immune dysregulation measurable through clinical, laboratory, biochemical, and immunological parameters. Knowledge Gap: However, early identification of patients at high risk of complications based on integrated clinico-immunobiochemical indicators has not been sufficiently systematized. Aims: This study aimed to determine the prognostic value of clinical and laboratory markers and to formulate preventive recommendations for early risk assessment in destructive cholecystitis. Results: In 111 patients, acute purulent-destructive cases demonstrated higher total cholesterol (7.81 ± 0.12 mmol/L), elevated LDL (3.44 ± 0.10 mmol/L), reduced HDL (0.89 ± 0.04 mmol/L), and markedly increased proinflammatory cytokines TNF-α (68.5 ± 2.74 pg/mL) and IL-6 (24.8 ± 1.12 pg/mL) compared with chronic cholecystitis and controls; imaging revealed more frequent gallbladder wall destruction, biliary hypertension, and ascites, accompanied by greater postoperative complication rates. Novelty: The study integrates cytokine profiling, lipid parameters, and instrumental findings into a unified clinico-immunobiochemical framework for early complication prediction. Implications: Comprehensive assessment of these markers supports personalized preventive strategies, optimized surgical planning, and timely identification of high-risk patients, thereby improving clinical decision-making and perioperative safety in destructive cholecystitis. Keywords: Destructive Cholecystitis, Cytokine Profile, TNF-α, Interleukin-6, Lipid Metabolism Key Findings Highlights: Acute purulent cases presented markedly higher proinflammatory mediator concentrations compared with chronic forms and controls. Dyslipidemia characterized by raised total cholesterol and LDL with decreased HDL distinguished severe disease groups. Combined laboratory and imaging indicators enabled earlier detection of patients prone to postoperative complications.